Reliability of the ERN across multiple tasks as a function of increasing errors. (30th July 2013) - Meyer, Alexandria; Riesel, Anja; Proudfit, Greg Hajcak
Abstract: Event‐related potential (ERP) studies of error‐processing have characterized the error‐related negativity (ERN) as a negative deflection occurring after the commission of an error at frontocentral sites. The ERN has frequently been examined in the context of individual differences and has been proposed as a neurobehavioral risk marker. Given this, it is important to characterize the psychometric properties of the ERN across multiple tasks as a function of increasing trial numbers in order to establish task‐specific psychometric properties for efficient assessments in clinical or applied settings. The current study examines the internal reliability of the ERN across the flankers, Stroop, and go/no‐go tasks as a function of error number. Results suggest that although the tasks all elicit the ERN reliably, important psychometric differences emerged indicating that the flankers task might be prioritized when assessing the ERN.